VD_FINDINFO HC / 2012 / 33 vom 9. Dezember 2011 - VD Tribunal cantonal (2011)
DÉPENS | 106 al. 1 CPC (CH), 106 al. 2 CPC (CH), 110 CPC (CH), 319 let. b ch. 1 CPC (CH), 320 CPC (CH), 321 al. 1 CPC (CH), 326 CPC (CH), 405 al. 1 CPC (CH)